Shared Genetics and Causality Between Decaffeinated Coffee Consumption and Neuropsychiatric Diseases: A Large-Scale Genome-Wide Cross-Trait Analysis and Mendelian Randomization Analysis - Yin, Bian; Wang, Xinpei; Huang, Tao; Jia, Jinzhu (Frontiers in Psychiatry, 2022)
Coffee or caffeine consumption has been associated with neuropsychiatric disorders, implying a shared etiology. However, whether these associations reflect causality remains largely unknown. To understand the genetic structure of the association between decaffeinated coffee consumption (DCC) and neuropsychiatric traits, we examined the genetic correlation, causality, and shared genetic structure between DCC and neuropsychiatric traits using linkage disequilibrium Score regression, bidirectional Mendelian randomization, and genome-wide cross-trait meta-analysis in large GWAS Consortia for coffee consumption (N=329,671) and 13 neuropsychiatric traits (sample size ranges from 36,052 to 500,199). We found strong positive genetic correlations between DCC and lifetime cannabis use (LCU) (Rg=0.48, P=2.52×10-19), alcohol use disorder identification test (AUDIT) total score (AUDIT_T) (Rg=0.40, P=4.52×10-13), AUDIT_C score (alcohol consumption component of the AUDIT) (Rg=0.40, P=2.00×10-12), AUDIT_P score (dependence and hazardous-use component of the AUDIT) (Rg=0.28, P=9.82×10-06) and strong negative genetic correlations between DCC and Neuroticism (Rg= -0.15, P=9.23×10-05), major depressed diseases (MDD) (Rg= -0.14, P=0.0016), and Insomnia (Rg= -0.13, P=0.0026). In the cross-trait meta-analysis, we identified 6, 5, 1, 1, 2, 32, and 28 shared loci between DCC and Insomnia, LCU, AUDIT_T, AUDIT_C, AUDIT_P, Neuroticism, and MDD respectively, which were mainly enriched in Bone marrow, lymph node, cervix, uterine, lung, and thyroid gland tissues and T cell receptor signaling pathway, antigen receptor-mediated signaling pathway and epigenetic pathways. A large of the TWAS-significant associations were identified in tissues that are part of the nervous system, digestive system, and Exo-/Endocrine System. Our findings further indicated a causal influence of liability to DCC on LCU and low risk of MDD (odds ratio: 0.90, P=9.06×10-5 and 1.27, P=7.63×10-4 respectively). We also observed that AUDIT_T and AUDIT_C were causally related to DCC (odds ratio: 1.83 per 1-SD increase in AUDIT_T, P=1.67×10-05, 1.80 per 1-SD increase in AUDIT_C, P=5.09×10-04). Meanwhile, Insomnia and MDD had a causal negative influence on DCC (OR:0.91,95% CI: 0.86-0.95, P=1.51×10-04 for Insomnia; OR: 0.93,95% CI:0.89-0.99, P=6.02×10-04 for MDD). These findings provided evidence for the shared genetic basis and causality between DCC and neuropsychiatric diseases, and advance our understanding of the shared genetic mechanisms underlying their associations, as well as assisting with making recommendations for clinical works.